MANAJEMEN BIDANG HUBUNGAN MASYARAKAT UNTUK MENINGKATKAN CITRA SMA - Eferi Eferi (UNIVERSITAS BENGKULU, 2015)
The purpose of this study is to describe the management of public relations in order to improve the image of State High School. This research is qualitative descriptive study. The method used is observation, interviews, and documentation. Data were collected and analyzed through data reduction, data presentation, and conclusions. The results showed that the management of public relations senior high school Number 5 Lubuklinggau country is already running and in places as it should. Communication between the school and the community applied to the form of support for public relations activities in improving the image of the school.Keywords: public relations and image management school